2011
DOI: 10.1136/ip.2010.028878
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric road traffic injuries in urban Ghana: a population-based study

Abstract: Childhood RTI in this urban west African setting are a major source of disability. Specific injury circumstances are reviewed in detail. This study provides baseline incidence data that may be used to measure injury prevention efforts and to validate secondary data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This finding is consistent with a Tanzanian study, 21 which reported that 93% of children involved in RTCs were pedestrians, and with a survey study in Ghana that found 78.5% of children involved in a road traffic injury were injured as pedestrians. 25 In this study, children were more likely to be involved in a crash in the early afternoon and evening, which are times consistent with Ghanaian reports on pediatric road injury. These data suggest that the times of day when children are struck may align with times when children are walking to and from school.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with a Tanzanian study, 21 which reported that 93% of children involved in RTCs were pedestrians, and with a survey study in Ghana that found 78.5% of children involved in a road traffic injury were injured as pedestrians. 25 In this study, children were more likely to be involved in a crash in the early afternoon and evening, which are times consistent with Ghanaian reports on pediatric road injury. These data suggest that the times of day when children are struck may align with times when children are walking to and from school.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Ackaah and Adonteng (2011) analysed RTC data for the period 2005–2007 and reported that pedestrians represented 42% of all road fatalities, with children accounting for one-third of all pedestrian fatalities. Other researchers have reported that child pedestrians are among the most vulnerable road users in Ghana (Aidoo et al, 2013; Guerrero et al, 2011). In addition, Damsere-Derry et al (2010) examined pedestrian crash data between 2002 and 2006.…”
Section: Introductionmentioning
confidence: 99%
“…12 More recently, population-based analyses of road traffic injuries in urban Tanzania 13 and urban Ghana 14 have further demonstrated that these injuries are a major source of disability in these settings. Together, these studies have helped to quantify the tremendous burden of morbidity and mortality associated with injuries in developing countries, and highlight the need for further data examining injuries on a larger scale.…”
Section: Introductionmentioning
confidence: 99%